Stakeholders Analysis For Creative Industry Development - Mangifera, Liana (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
The regional industry of Sukoharjo Regency is dominated by the manufacturing sector. Sukoharjo Regency has many creative industry potentials such as wood, rattan, gamelan, batik, leather, and glass grafir. Stakeholders have an important role in the development of creative industry. The various roles and interests of stakeholders must be well managed for the optimization of the program of developing the creative industry. This study aims to identify the stakeholders involved in the development of creative industry, describe the various interests of stakeholders in the creative industry and formulate strategies for developing creative industry in Sukoharjo regency. This research use mixed method. Descriptive analysis to explain the types and interests of stakeholders involved in the creative industry in Sukoharjo District, and to explain the strategy of developing creative industry. Quantitative analysis in this study uses stakeholder analysis that is used to explain the relationship and the role of stakeholders in the development of creative industry. The results show that not all stakeholders are actively involved in the development of creative industry and every stakeholder has different interests. To optimize the development of creative industry hence needed a forum as communication container for coordination among stakeholders in creative industry development in Sukoharjo regency.